2019
DOI: 10.1038/s41598-019-49636-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin modulates the temporal dynamics of resting EEG networks

Abstract: Oxytocin is a key modulator of social interaction, but we possess little knowledge of its underlying effects on neuropsychological processes. We used a spatio-temporal EEG microstates analysis to reveal oxytocin’s effects on the temporal dynamics of intrinsically generated activity in neural networks. Given oxytocin’s known anxiolytic effects, we hypothesized that it increases the temporal stability of the four archetypal EEG resting networks. Eighty-six male participants had received oxytocin or placebo intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 72 publications
4
42
2
1
Order By: Relevance
“…In support of this conceptualization higher temporal flexibility 347 of the brain has been associated with the motor-skill learning ability (Bassett et al, 2011(Bassett et al, , 2013(Bassett et al, , 348 2015 and general intelligence (Zhang et al, 2016) and has been found to be impaired across 349 psychiatric disorders characterized by cognitive and social impairments (Zhang et al, 2016). 350 However, in contrast to a previous pharmacological EEG study (Schiller et al, 2019), we found 351 no evidence of OXT influencing brain temporal state switching frequency. This may perhaps 352 reflect the fact that the peptide has no reported effects on either motor learning or general 353 intelligence, although since it does influence learning with social feedback and rewards 354 (Hurlemann et al, 2010;Hu et al, 2015) and it is possible that it might influence switching 355 frequency during performance of such social learning tasks.…”
contrasting
confidence: 92%
“…In support of this conceptualization higher temporal flexibility 347 of the brain has been associated with the motor-skill learning ability (Bassett et al, 2011(Bassett et al, , 2013(Bassett et al, , 348 2015 and general intelligence (Zhang et al, 2016) and has been found to be impaired across 349 psychiatric disorders characterized by cognitive and social impairments (Zhang et al, 2016). 350 However, in contrast to a previous pharmacological EEG study (Schiller et al, 2019), we found 351 no evidence of OXT influencing brain temporal state switching frequency. This may perhaps 352 reflect the fact that the peptide has no reported effects on either motor learning or general 353 intelligence, although since it does influence learning with social feedback and rewards 354 (Hurlemann et al, 2010;Hu et al, 2015) and it is possible that it might influence switching 355 frequency during performance of such social learning tasks.…”
contrasting
confidence: 92%
“…This is also consistent with the results of Seitzman et al showing that microstate type D is task-positive, and microstate type C is task-negative 27 . In both groups, the mean duration and mean occurrence changed, which suggests that there was a change in temporal stability due to task execution 28 . However, poor performers had a different degree of change compared to good performers.…”
Section: Discussionmentioning
confidence: 93%
“…Our measurement protocol consisted of 20-s eyes open periods followed by 40-s eyes closed periods, repeated five times. This resting state paradigm has been routinely used in resting EEG research 16,17,27,77 in order to minimize fluctuations in participants' vigilance state. Participants can become drowsy already after 3 min of recording resting state brain activity, if there is no alternation of eyes-open/eyes-closed periods 78 .…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, we used a spatio-temporal analysis approach to cluster the resting EEG signal into a circumscribed number of scalp electrical potential topographies that remain stable for certain time periods (ca. 50-120 ms) before dynamically changing into a different topography that remains stable again [24][25][26][27][28] . One has referred to these periods with stable topographies as "microstates" and one has interpreted transitions between microstates to represent sequential coordinated activity of different, distributed neural networks.…”
mentioning
confidence: 99%